2021
DOI: 10.1021/acs.jafc.1c04194
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein Enhances the Effect of Acarbose on the Improvement of Nonalcoholic Fatty Liver Disease Associated with Prediabetes via the Inhibition of De Novo Lipogenesis

Abstract: Prediabetes is a prevalent metabolic disorder with multiple complications, including nonalcoholic fatty liver disease (NAFLD). In this study, we investigated the combinatorial effect of baicalein, a dietary flavonoid abundant in multiple edible plants, and acarbose on prediabetes-associated NAFLD. Baicalein and its metabolites inhibited de novo lipogenesis (DNL), thereby decreasing lipid accumulation and hepatokine secretion in oleic acid-induced hepatocytes. Carbohydrate restriction, which mimicked the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 48 publications
4
20
0
Order By: Relevance
“…It is evidence that indicated that BAL inhibits hepatic de novo lipogenesis via suppressing SREBP1c and ChREBP activities, thereby reversing the high expressions of FASN, ACC and SCD expression in oleic acid-induced hepatocytes and highfat-diet (HFD) induced mice (Xing et al, 2021), we got the similar results in fructose-induced rats. These evidences suggested that excessive HFD or fructose consumption both enhance the activities of key regulators in hepatic DNL, SREBP1c and ChREBP in liver, and which were suppressed by BAL treatment.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…It is evidence that indicated that BAL inhibits hepatic de novo lipogenesis via suppressing SREBP1c and ChREBP activities, thereby reversing the high expressions of FASN, ACC and SCD expression in oleic acid-induced hepatocytes and highfat-diet (HFD) induced mice (Xing et al, 2021), we got the similar results in fructose-induced rats. These evidences suggested that excessive HFD or fructose consumption both enhance the activities of key regulators in hepatic DNL, SREBP1c and ChREBP in liver, and which were suppressed by BAL treatment.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, Oil red O (ORO) Staining was also used to investigate the hepatic lipid accumulation in fructose-fed rats. As previous descriptions with a little adjustment (Li L. et al, 2021), liver tissues were fixed with 4% paraformaldehyde and put the tissues in 15-30% sucrose solution for dehydrating twice at 4 °C. After that, embedding agent were used to embed.…”
Section: Histological Examinationmentioning
confidence: 99%
“…Therefore, the hypothesis that whether the effective control of liver fatty acid synthase and the promotion of fatty acid β-oxidase activity are potential means to alleviate the abnormal accumulation of lipid droplets and TG can be supported by evidence in recent studies . Studies have shown that, in the study of food ingredients, it was found that the combination of baicalein and acarbose could inhibit de novo lipogenesis and the expression of synthase . Interestingly, our results also provided theoretical support for this hypothesis; specifically, Ery inhibited the activity of FAS, ACC, and SREBP-1c and promoted the expression of PPAR α, CPT1A , CPT2 , and ACO in the NAFLD model in vivo and in vitro.…”
Section: Discussionsupporting
confidence: 76%
“…20 Studies have shown that, in the study of food ingredients, it was found that the combination of baicalein and acarbose could inhibit de novo lipogenesis and the expression of synthase. 17 Interestingly, our results also provided theoretical support for this hypothesis; specifically, Ery inhibited the activity of FAS, ACC, and SREBP-1c and promoted the expression of PPARα, CPT1A, CPT2, and ACO in the NAFLD model in vivo and in vitro.…”
Section: ■ Discussionsupporting
confidence: 72%
See 1 more Smart Citation